How do you differentiate f(x)=(cosx-x)/(sin3x-x^2)f(x)=cosxxsin3xx2 using the quotient rule?

1 Answer
Mar 5, 2017

((-sinx-1)(sin3x-x^2)-(3cos3x-2x)(cosx-x))/(sin3x-x^2)^2(sinx1)(sin3xx2)(3cos3x2x)(cosxx)(sin3xx2)2

Explanation:

The quotient rule states that

d/dx f(x)/g(x) = (f'(x)g(x)-g'(x)f(x))/g^2(x)

Here,

f(x) = cosx-x

so

f'(x) = d/dx[cosx]-d/dx[x] = -sinx-1

and

g(x) = sin3x - x^2

so

g'(x) = d/dx[sin3x]-d/dx[x^2] = 3cos3x-2x

We can put these functions into the formula for the quotient rule:

d/dx f(x)/g(x) = ((-sinx-1)(sin3x-x^2)-(3cos3x-2x)(cosx-x))/(sin3x-x^2)^2

which you could expand out to give

= (-sinxsin3x+x^2sinx-sin3x+x^2-3cosxcos3x+3xcos3x+2xcosx-2x^2)/(sin^2(3x)-2x^2sin3x+x^4)

though this is more complicated and unnecessary.